IMPLIKASI MODEL PEMBELAJARAN BLENDED LEARNING BAGI PELAKSANAAN PEMBELAJARAN DI SMP KATOLIK YOHANES GABRIEL PARE - Diky Indra Atmaja; Agustinus Supriyadi (Bahasa Indonesia, 2022)
Blended learning is a learning model that combines face-to-face learning with web-based learning, by utilizing media and tools that can be used in an e-learning learning environment. The hope with the blended learning model is that educators must be ready and brave to face technological advances and students to be active and independent. The blended learning model is also applied to Catholic schools, including Yohanes Gabriel Pare Catholic Junior High School. The purpose of this study (1) is to describe what is meant by a blended learning model. (2) Explaining the implications of the blended learning model for the implementation of learning in Yohanes Gabriel Pare Catholic Junior High School. This study uses a qualitative method. The respondents of this research were the teachers of Yohanes Gabriel Pare Catholic Junior High School. The number of respondents in this study was 10 people. From the results of this study, John Gabriel Pare Catholic Junior High School teachers revealed that the function of digital learning in learning activities in the classroom is as a complement or complement